The fuzzy front end of innovation - Óskarsson, Gunnar (Henry Stewart Talks, 2015)
Environment for innovation, Performance in innovation processes, Front end of innovation, Culture for innovation, Knowledge integration, Interaction with suppliers, Market orientation, Customer involvement, Communication processes, Innovation capability, Innovativeness, Radical and incremental innovation, Managerial IT skills, The role of leaders in innovation